2008
DOI: 10.1111/j.1949-8594.2008.tb17836.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Representations of Flu and Microbial Illness Held by Students, Teachers, and Medical Professionals

Abstract: This study describes 5 th, 8th, and 11th‐grade students', teachers', and medical professionals' conceptions of flu and microbial illness. Participants constructed a concept map on “flu” and participated in a semi‐structured interview. The results showed that these groups of students, teachers and medical professionals held and structured their conceptions about microbes differently. A progression toward more accurate and complete knowledge existed across the groups but this trajectory was not always a predicta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Despite opportunities to integrate scale concepts into a diversity of science domains it is often difficult for students (let alone their teachers) to master these ideas (Tretter et al 2006a). For example, students in elementary and middle school think that a virus is larger than a bacterium because they perceive that it is more virulent (Jones and Rua 2008). Other studies have shown that students struggle with conceptualizing the size of red blood cells or the size of DNA (Delgado 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Despite opportunities to integrate scale concepts into a diversity of science domains it is often difficult for students (let alone their teachers) to master these ideas (Tretter et al 2006a). For example, students in elementary and middle school think that a virus is larger than a bacterium because they perceive that it is more virulent (Jones and Rua 2008). Other studies have shown that students struggle with conceptualizing the size of red blood cells or the size of DNA (Delgado 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Simonneaux (2000) examined students' concepts of the immune system in the context of biotechnology through interviews and reported that students' knowledge was fragmentary and varied from notions that the immune system eliminates dirt from the body to ideas that the immune system protects the body from impurities. A previous study of elementary, middle, and high school students and teachers, along with medical professionals (Jones & Rua, 2008) found that elementary and middle school students appeared to have very few concepts of immunity and high school students and adults had only limited knowledge of immunity. Several studies have shown that students' knowledge of antibodies and antibiotics are often inaccurate.…”
Section: Immune Systemmentioning
confidence: 96%
“…In a previous study, Jones and Rua (2008) found that students did not associate vaccinations directly with viruses. Some elementary and middle school students tended to think a vaccination was like a pain killer or had disinfectant properties similar to soap.…”
Section: Vaccinationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Data from the card sort task were analyzed using multi-dimensional scaling methods (Jones and Rua 2008;Tsogo and Masson 2000). The output of multi-dimensional scaling analyses is a spatial representation of the similarity of the biotechnology applications in n-dimensional space with each point corresponding to a particular application.…”
Section: Rps: Psychometric Paradigm Assessmentmentioning
confidence: 99%